Avaliação da relação entre a temperatura da superficie corporal e produção de vacas jersey submetidas à climatização na pré-ordenha - Laloni, Luis Antonio; Naas, Irenliza Alencar de [UNESP]; Macari, Marcos [UNESP]; Pinheiro, Maria da Graça; Pereira, Danilo Florentino [UNESP] (My University, 2002)
Jersey cows has been used in warm climates because they have better performance in dairy production. Generally milk production is reduced in warm climates due to the consequent reduction in feed intake because of the heat stress. When the heat stress occurs there is an increase in the body temperature, however it is not known if the skin temperature indicates a thermal discomfort or if it influences milk yield. The objective of this research was to verify if there was a correlation between skin temperature and milk yield using two treatments. Treatment (A) where the cows stayed for 30 minutes before the milking period, in a room with a shower and a fan; and treatment (B) where the cows did not had access to any cooling device (control). After milking the skin temperature were recorded in the places: forehead, back, leg and teats. Data were statistically analyzed and, even though in treatment (A) the skin temperature were reduced it was not found correlation between skin temperature and milk yield.
Evaluating the relationship between superficial body temperature and milk yield in lactating jersey cows using climatization at pre-milking parlor
Keywords: Body temperature; Environment; Jersey cows; Climatology; Cooling systems; Data reduction; Statistical methods; Thermal stress; Dairy products